wisePad Services for Vision-,Hearing-,and Speech-Impaired Users. - JUTLA, DAWN N.; KANEVSKY, DIMITRI (Communications of the ACM, 2009)
The article discusses wisePad services, defined as full-service computing platforms which are designed to assist people with hearing problems, impaired vision, or people needing assistance with spoken and text-based language. These platforms will provided personalized image-, audio-, and text-transformation services to such individuals, the article states. Other topics include magnified images for people with impaired vision, speech transformed into text of another language, and glasses with frames big enough to hold a small USB (Universal Serial Bus) port.